Characteristics of Indian Traditional Costumes and its Application in Contemporary Fashion Design as a Cross-Cultural Phenomenon - Shukla, Anshika; Park, Hyewon (International Journal of Costume and Fashion, 2023)
This study deals with the ongoing trend of cross-cultural phenomenon as a hybrid trend in fashion and examines the cross-culture of luxury fashion brands and Indian traditional costumes that has become a new source of attraction for designers in the fashion industry. Indian traditional costumes serve as a potential source of inspiration in the global fashion industry but it has not penetrated significantly. The motive of this study is to scrutinize the characteristics of Indian traditional costumes and derive their meaning to identify how these elements have inspired designers on the contemporary fashion stage by focusing on three design collaborations- Dior and Chanakya, H&M and Sabyasachi, and Suketdhir and Banarasi Weaves. First, it identifies how Indian traditional costumes have influenced different fashion segments in terms of fusion wear, designer collaborations, bollywood movie costume, as well as sustainable fashion. It then employs an image analysis of 30 fashion collaboration images. From the analysis, it derives the characteristics of Indian Traditional Costumes that act as a source of inspiration for the fashion brands. Ultimately, this research will form the basis for future studies as it gives a detailed outline of Indian Costumes, paving new forms of globalization and cultural exchange. KCI Citation Count: 0